2022
DOI: 10.1038/s41589-021-00951-y
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid conformation-dependent disaggregation in a reconstituted yeast prion system

Abstract: Disaggregation of amyloid brils is a fundamental biological process required for amyloid propagation.However, due to the lack of experimental systems, the molecular mechanism of how amyloid is disaggregated by cellular factors remains poorly understood. Here, we established a robust, in vitro reconstituted system of yeast prion propagation and found that Hsp104, Ssa1, and Sis1 chaperones are essential for e cient disaggregation of Sup35 amyloid. Real-time imaging of single-molecule uorescence coupled with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…More recent work by Son and Wickner has demonstrated that most [ PSI + ] variants (amyloid polymorphisms) that arise in the absence of RAC can be cured by normal levels of Zuo1 and Ssz1 22 . Indeed, the de novo formation of prions depends on the balance between amyloid seed nucleation and clearance, and chaperones such as the disaggregase Hsp104 and the Hsp70/40 pair Ssa1 and Sis1 play critical roles in yeast prion propagation 33,34 . Amyloid disaggregation by Hsp104 can lead to either fragmentation (which enables propagation) or dissolution, and the presence of the prion form of Rnq1 (termed [ PIN + ] or [ RNQ + ]) was shown to promote [ PSI + ] formation by titrating Hsp104 activity on Sup35 amyloid 33 .…”
Section: Discussionmentioning
confidence: 99%
“…More recent work by Son and Wickner has demonstrated that most [ PSI + ] variants (amyloid polymorphisms) that arise in the absence of RAC can be cured by normal levels of Zuo1 and Ssz1 22 . Indeed, the de novo formation of prions depends on the balance between amyloid seed nucleation and clearance, and chaperones such as the disaggregase Hsp104 and the Hsp70/40 pair Ssa1 and Sis1 play critical roles in yeast prion propagation 33,34 . Amyloid disaggregation by Hsp104 can lead to either fragmentation (which enables propagation) or dissolution, and the presence of the prion form of Rnq1 (termed [ PIN + ] or [ RNQ + ]) was shown to promote [ PSI + ] formation by titrating Hsp104 activity on Sup35 amyloid 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in yeast showed the maintenance and propagation of three prions associated with Rnq1, Ure2, and Sup35 are dependent on an Hsp40 family protein Sis1 (Aron et al, 2007; Higurashi et al, 2008; Lopez et al, 2003). Sis1 acts as a disaggregase in collaboration with Hsp104 and Hsp70 by helping in the fragmentation of the oligomers of these prions to generate propagating seeds (Nakagawa et al, 2022). Another Hsp40 family protein Ydj1 together with Hsp70 has been found to inhibit the formation of Ure2 prion state in yeast by delaying its aggregation to form amyloid fibrils (Lian et al, 2007; Sharma et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fragmentation of the Sup35 prion relies on sequential action of chaperones Sis1, Ssa and Hsp104 [ 113 ]. It is known that overproduction of Hsp104 does not improve fragmentation of Sup35 [ 114 ].…”
Section: Sup35 Variant Prion Structuresmentioning
confidence: 99%
“…Sis1 chaperone dimer is likely to be present at one per ten protomers, and the Ssa chaperones at one per two protomers [ 27 , 112 ], but only half of Ssa molecules are shown. Though a recent in vitro study on Sup35 fibrils suggested a ratio of one Sis1 dimer to two Ssa, these data were not directly quantified [ 113 ]. Hsp104 hexamer and the ribosome outline are shown.…”
Section: Sup35 Variant Prion Structuresmentioning
confidence: 99%